2018
DOI: 10.3168/jds.2017-13249
|View full text |Cite
|
Sign up to set email alerts
|

Feed substrates influence biofilm formation on reverse osmosis membranes and their cleaning efficiency

Abstract: The dairy industry is increasingly using reverse osmosis (RO) membranes for concentration of various fluid feed materials such as whey and ultrafiltration (UF) permeate. This study compared the effect of UF permeate and whey on membrane biofilm formation. A Bacillus sp., previously isolated in our laboratory from a cleaning-resistant membrane biofilm, was used to develop 48-h-old static biofilms on RO membrane pieces, using the different feed substrates (UF permeate, whey, and an alternating whey/UF feed). Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…The obtained data were consistent with the findings of Marka and Adand [15]. The authors found that during the processing of skimmed milk permeate, biofilms on reverse osmosis membranes formed faster than during processing of sweet whey.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The obtained data were consistent with the findings of Marka and Adand [15]. The authors found that during the processing of skimmed milk permeate, biofilms on reverse osmosis membranes formed faster than during processing of sweet whey.…”
Section: Resultssupporting
confidence: 91%
“…According to Marka and Anand, biofilms of sweet whey were less resistant to standard CIP washing than biofilms of skimmed milk. Noteworthily, these results were obtained in the study on reverse osmosis membranes, with the processing of raw materials lasting 48 hours and the washing conditions being different [15].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The cost for chemical expenses is related to control of membrane fouling, which decreases water permeate flux as the foulants deposit onto membranes and feed spacers during operation [43][44][45][46][47]. Membrane fouling may be classified into four types: organic fouling, particulate fouling, biological fouling, and inorganic fouling (scaling) [47][48][49]. Particulate fouling represents the deposition of aluminum silicate, clays, colloids, sand, and silt [47].…”
Section: Introductionmentioning
confidence: 99%